Institutional governance and financial sector development: Panel evidence from Asian economies - Nazima Ellahi; Adiqa Kiani; Qaisar Ali Malik; Asif Raza; Raazia Gul (Cogent Economics & Finance, 2021)
Current study aims to investigate the impact of institutional governance (GOV), trade openness (TOPEN), real output (RGDP), economic freedom (EFR), inflation rate (INFR) and real output growth on financial sector development (FSD) of selected Asian economies. A consolidated financial sector development index, representing banking sector and stock market is generated using Principal Component Analysis (PCA). The study conducted data analysis by applying panel estimation method of Generalized Method of Moments (GMM), and showed that trade openness, and real output moderate the financial development (FSD) through its positive interaction with institutional governance (GOV). The findings highlight that governance is an important and crucial driver of financial sector development and stock market development in four selected Asian economies.
Keywords: 330; economic freedom; generalized method of moments & financial development; Institutional governance